PENGARUH LITERASI KEUANGAN DAN TEMAN SEBAYA TERHADAP PERILAKU MENABUNG DENGAN MINAT MENABUNG SEBAGAI VARIABEL INTERVENING - Muhammad Syaiful Anam; Bambang Sunatar; Syahrul Syahrul; Andi Hasrun; La Ode Obi (LPPM STIE Muhammadiah Bandung, 2026)
This study aims to analyze the effect of financial literacy and peer influence on saving behavior with saving intention as an intervening variable among KIP Kuliah scholarship recipients at the IAIN Sorong. This research employed a quantitative descriptive approach. The population consisted of 625 active KIP Kuliah scholarship students from the 2023-2025 academic years, with a sample of 86 respondents selected using the Sloving formula and purposive sampling technique. Data were collected through questionnaires using a five-point Likert scale and analyzed using SmartPLS4. The result indicare that financial literacy has a positive and significant effect on saving intention and saving behavior. Peer influence has a positive and significant effect on saving intention but does not have a direct significant effect on saving behavior. Futhermore, saving intention has a positive and significant effect on saving behavior. Mediation analysis reveals that saving intention partially mediates the relationship between financial literacy and saving behavior, while fully mediating the relationship between peer influence and saving behavior. These findings suggest that saving intention plays a crucial role in shaping students saving behavior, while financial literacy and peer influence function as antecedent factors that enhance saving intention).